2019
DOI: 10.3389/fvets.2019.00178
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Chondrogenic Differentiation Potential of Equine Synovial Membrane-Derived and Bone Marrow-Derived Mesenchymal Stem Cells

Abstract: Focal cartilage injury occurs commonly and often precipitates OA. Mesenchymal stem cells (MSCs) may be useful for repairing cartilage lesions, thereby preventing joint degeneration. Although MSCs isolated from bone marrow have been shown to have chondrogenic potential, synovial membrane-derived MSCs (SM-MSCs) may have superior chondrogenic abilities due to a common progenitor cell between synovium and cartilage. The objective of this study was to directly compare the immunophenotype, proliferative capabilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…However, when articular cartilage is injured, spontaneous repair is very difficult because the perichondrium covering the articular cartilage surface is absent, bone progenitor cells are lost and the synthesis capacity of the chondrocytes adjacent to the injured site is limited 34 . Currently, BMSCs, adipose tissue-derived mesenchymal stem cells 35 , synovial mesenchymal stem cells 36 , and embryonic mesenchymal stem cells 37 can be used as seed cells for tissue-engineered cartilage repair. Here, we demonstrated that pBMSCs have a great ability to differentiate into chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, when articular cartilage is injured, spontaneous repair is very difficult because the perichondrium covering the articular cartilage surface is absent, bone progenitor cells are lost and the synthesis capacity of the chondrocytes adjacent to the injured site is limited 34 . Currently, BMSCs, adipose tissue-derived mesenchymal stem cells 35 , synovial mesenchymal stem cells 36 , and embryonic mesenchymal stem cells 37 can be used as seed cells for tissue-engineered cartilage repair. Here, we demonstrated that pBMSCs have a great ability to differentiate into chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have proven that SDSCs possess a stronger capacity for proliferation and chondrogenic differentiation than BMSCs and ADSCs 16 , 38 , 95 , 96 , while their osteogenic capability has been shown to be weaker than that of BMSCs. In addition, the expression of MSC markers (CD105, CD90, CD73, MHC-I) was similar between SDSCs and BMSCs, but MHC-II expression was much lower in SDSCs 97 , indicating that SDSCs also possessed an advantage in terms of immunogenicity. Djouad reported that the immunomodulatory ability of SDSCs was comparable to that of BMSCs.…”
Section: Tissue Source-dependent Variation In Mscs For Cartilage Repamentioning
confidence: 92%
“…Bone marrow stem cells are the typical donor cells of exosomes, and miRNAs are the typical therapeutic cargoes [85]. SF-MSCs have shown higher chondrogenic potential than BM-MSCs [86]. Exosomes purified from autologous SF-MSCs represent exciting new avenues to deliver miRNAs in OA treatment (Fig.…”
Section: Mir-140 Delivery By Exosomesmentioning
confidence: 99%